Morphology, ultrastructure and function of the sternal gland in two mason bee species (Osmia bicornis and O. cornuta) - Stephanie Krüger; Karsten Seidelmann (PLoS ONE, 2025)
Pheromonal communication is often facilitated by the evolution of specialized gland structures. Males of two species of mason bees release specific carboxylic esters from a hidden sternal gland. This gland tissue consists of a single layer of class 1 secretory cells located on two sternites. The unmodified cuticle above the gland tissues is dented and covered with setae. Together with the elongated covering sternite, these depressions form a storage vessel for volatiles. This gland morphology facilitates the slow, continuous release of volatiles through leakage from the cavity, as well as the enhanced, voluntary release of higher concentrated pheromone puffs through abdominal movements. The carboxylic esters released from the gland have a deterrent effect and indicate the sex of the male from a distance. Pheromone puffs emitted by abdominal movements enable mating to occur without interference from competitors. In this context, the carboxylic esters act as antiaphrodisiacs.